Evaluation of the deuterium isotope effect in zwitterionic hydrophilic interaction liquid chromatography separations for implementation in a quantitative proteomic approach. - Di Palma, S; Raijmakers, R; Heck, A; Mohammed, S (2011)
Quantitative methodologies for the global in-depth comparison of proteomes are frequently based on chemical derivatization of peptides with isotopically distinguishable labeling agents. In the present work, we set out to study the feasibility of the dimethyl labeling method in combination with ZIC-cHILIC (zwitterionic hydrophilic interaction liquid chromatography) technology for quantitative proteomics. We first addressed the potential issue of isotope effects perturbing the essential coelution of differently labeled peptides under ZIC-cHILIC separation. The deuterium incorporation-induced effect can be largely eliminated by favoring the mixed-mode ZIC-cHILIC separation based on combined hydrophilic and ionic interactions. Then, we evaluated the performance and applicability of this strategy using a sample consisting of human cell lysate. We demonstrate that our approach is suitable to perform unbiased quantitative proteome analysis, still quantifying more than 2500 proteins when analyzing only a few micrograms of sample.